1999
DOI: 10.1021/cm991018f
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Internal Spin Canting in γ-Fe2O3 Nanoparticles

Abstract: Structural and magnetic properties of γ-Fe2O3 have been studied in isometric nanoparticles ranging from 3 to 14 nm with a narrow particle size distribution. Cation vacancy order is observed for particles larger than 5 nm in diameter giving rise to a cubic superstructure, while for the smallest particles these vacancies are disordered. All magnetic properties measured showed a strong dependence on the average crystallite size. For the ordered samples, saturation magnetization was found to decrease linearly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
456
4
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(508 citation statements)
references
References 21 publications
38
456
4
7
Order By: Relevance
“…147 Uniform and well-crystallized nanoparticles are synthesized in a single step. 98 The high production rates of these methods come at the cost exhaustive control over experimental conditions and expensive equipment.…”
Section: Additional Methodsmentioning
confidence: 99%
“…147 Uniform and well-crystallized nanoparticles are synthesized in a single step. 98 The high production rates of these methods come at the cost exhaustive control over experimental conditions and expensive equipment.…”
Section: Additional Methodsmentioning
confidence: 99%
“…For example, M s decreases linearly for magnetite/maghemite nanoparticles with decreasing crystallite size (77 and 12 A m 2 kg −1 for particles of 13.5 and 4 nm in diameter, respectively) due to surface and internal spin canting (cation vacancy order-disorder) (36). The high field irreversibility observed for samples at t ¼ 0 and 1 h, which is closely related to the existence of a certain degree of magnetic disorder, supports this assumption.…”
Section: Si Appendix)mentioning
confidence: 99%
“…As discussed earlier (Figure 2(b)), by increasing the calcination temperature of the MnFe 2 O 4 nanoparticles, Fe 3+ ions transferred from B site to A site, so, consequently, the accumulation of Fe 3+ ions increased in A site; however, the Fe A 3+ -Fe B 3+ superexchange interactions increased (Fe A 3+ -Fe B 3+ interactions were twice as strong as the Mn A 2+ -Fe B 3+ interactions), and this can lead to an increase in saturation magnetization in MnFe 2 O 4 nanoparticles [34]. Aslibeiki et al [35] showed that saturation magnetization increases with increasing temperature and particle size in MnFe 2 O 4 nanoparticles.It has been reported [36] that the spin disorder may occur on the surface of the nanoparticles as well as within the cores of the nanoparticles due to vacant sublattice disorder sites (Fe A 3+ ) and poor crystal structure. The other point that is understood from Table 1 is that the values of saturation magnetization are expressively lower than those reported for the bulk MnFe 2 O 4 (80 emu/g) [37].…”
Section: Phase Composition and Morphology Of Precursors Andmentioning
confidence: 99%